2022
DOI: 10.3390/biomedicines10020349
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin Modulation and Inter-Cellular Trafficking in Tubular Gastric Adenocarcinoma: A High-Resolution Microscopy Pilot Study

Abstract: Despite the numerous advances in tumor molecular biology and chemotherapy options, gastric adenocarcinoma is still the most frequent form of gastric cancer. One of the core proteins that regulates inter-cellular adhesion, E-cadherin plays important roles in tumorigenesis as well as in tumor progression; however, the exact expression changes and modulation that occur in gastric cancer are not yet fully understood. In an attempt to estimate if the synthesis/degradation balance matches the final membrane expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Epigenetic alterations have been shown to lead to CDH1 inactivation through an array of complex mechanisms. For instance, low E-cad expression in GC has been linked with methylation of CDH1 CpG islands, indicating that the CDH1 promoter methylation might be a critical molecular event in the initiation of GC (16). In addition, we showed that the methylation rate of CDH1 promoter in gastric carcinoma was higher than that in non-cancerous specimens, thus inactivation of the CDH1 by methylation could result into GC.…”
Section: Discussionmentioning
confidence: 81%
“…Epigenetic alterations have been shown to lead to CDH1 inactivation through an array of complex mechanisms. For instance, low E-cad expression in GC has been linked with methylation of CDH1 CpG islands, indicating that the CDH1 promoter methylation might be a critical molecular event in the initiation of GC (16). In addition, we showed that the methylation rate of CDH1 promoter in gastric carcinoma was higher than that in non-cancerous specimens, thus inactivation of the CDH1 by methylation could result into GC.…”
Section: Discussionmentioning
confidence: 81%